Keanekaragaman Tanaman Pekarangan dan Pemanfaatannya untuk Mendukung Ketahanan Pangan Kecamatan Wakorumba Selatan - . Feriatin (Institut Pertanian Bogor, 2017)
This study aimed to determine the type composition, vegetation structure, and the patterns of utilization to support food security in the sub district of South Wakorumba. This study employed a quadrat method. The results of this research show that the composition of plant species in gardens in South Wakorumba sub district was comprised of 25 families from 44 species of plants. For plants vegetation structure the highest of importance value for trees of the class was indicated by coconut (Cocos nucifera L.) species. Whereas the lowest value was indicated by water apple (Eugenia aquea Burm. F) species. For of poles, the highest of importance value was indicated by chocolate (Theobroma cacao L.) species. Whereas the lowest value was by Jamaica cashew (Syzygium malacensis) species. The class of saplings highest value was indicated by papaya (Carica papaya L.) species. whereas the lowest was indicated by tamarind (Tamarindus indica L.) species. For of seedling the highest of importance value was indicated by coconut (Cocos nucifera L.) species. Whereas the lowest of importance value was indicated by rambutan (Nephelium lappaceum L.) species. The pattern of utilization of garden plants by the villagers of Wakorumba Sub District is as follows: as a source of carbohydrate (18.18%), proteins (11.36%), vitamins (45.45%), minerals (22.73%), and fat (2.27%)